DESAIN PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI SISWA: A LITERATUR REVIEW - Muhammad Arbi; Synthia Ferisca; Nuraini Safitri; Muhamad Khanif Istakhori; Galih Prayoga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Literacy and numeracy skills are essential competencies for students to face the challenges of the 21st century. However, research findings indicate that students' literacy and numeracy skills in Indonesia still need improvement. Problem-Based Learning (PBL) can serve as an alternative model to help enhance students' literacy and numeracy skills through a student-centered learning process. This study aims to conduct a literature review focusing on the design and implementation of PBL in improving students' literacy and numeracy skills. The method used is a literature study with four main stages: determining the theme, searching and selecting literature, analyzing and synthesizing literature, and organizing the writing. The literature review results show that PBL can encourage students to be more active, think critically, and collaborate, which can contribute to enhancing literacy and numeracy skills. Furthermore, the literature review identifies factors that may influence the successful implementation of PBL, including the role of teachers, availability of resources, student engagement, and school policies. This literature review is expected to provide insights for teachers to optimize problem-based learning as an effort to improve students' literacy and numeracy skills.